5PSQ-080 Assessment of dose preparation practices from liquid oral forms by mothers of children hospitalised in our paediatric department. (24th March 2020) - Nchinech, N; Attjioui, H; Aglili, FZ; Kriouile, Y; Alaoui Mdaghri, A; Cherrah, Y; Serragui, S
Abstract : Background and importance: In our paediatric department, we welcome low income populations, it is the mothers who take care of the administration of oral treatments to their children. Because of the high rate of illiteracy among these mothers, this situation can lead to administration errors, particularly when it comes to oral presentations with a liquid administration device. Aim and objectives: To study the dose preparation errors of liquid oral forms by the mothers of hospitalised children. Material and methods: This prospective observational study was conducted in our paediatric department, between March and June 2019. During this period, interviews including a questionnaire in dialectal Arabic on how to use the liquid oral forms they administer to their children (administration schedule, preservation and interchangeability of graduated pipettes) were conducted. Subsequently, the preparation of drug intake of the two most prescribed liquid oral presentations in the department was implemented: Amoxil (amoxicillin, measuring spoon) and Azimax (azithromycin, dose weight pipette). Results: A total of 77 mothers were included in the study. More than 75% (n=58) showed poor understanding of the intake method when we tried to have them repeat the dosing and administration schedule compared with the medical prescriptions they had. For 75.55% of the 45 mothers with a prescription containing Amoxil, the oral suspension, once reconstituted, was stored at room temperature when it required refrigeration (2–8°C). The response for the preservation of the two drugs after opening the vials was until expiration in 92.20% (n=71), while actually it is 7 days for Amoxil and 5 days for Azimax. Seventy-two interviewees thought that it was possible to exchange graduated pipettes. The Amoxil and Azimax reconstitutions were incorrect in 66.66% (30/45) and 81.25% (26/32) of cases, respectively, with the risk of overdose for Azimax (15/26) and underdosage for Amoxil (19/30). The preparation of the dose was incorrect in 60% of cases when using the dosing spoon with Amoxil and in 84.37% of cases when using the dosing pipette with Azimax. Conclusion and relevance: This study highlights the significant number of errors made by mothers during reconstitution and preparation of drugs, which requires the hospital pharmacist's involvement in educating families on the use of liquid oral forms. References and/or acknowledgements: No conflict of interest.